PERLINDUNGAN HUKUM BAGI MASYARAKAT DALAM PELAKSANAAN PEMBATASAN SOSIAL BERSKALA BESAR DI KOTA AMBON - D. Bakarbessy, Andress; Soplanit, Miracle; S. Alfons, Saartje (Universitas Ekasakti, 2021)
The implementation of the PSBB in the city of Ambon has received various criticisms from the public, there have been various actions by the community that have disobeyed the PSBB guardian, as well as problems with law enforcement by law enforcement officials. The purpose of the study was to examine and analyze the effectiveness of the implementation of PSBB in Ambon City and to examine and analyze legal protection for the people of Ambon City in implementing PSBB. The research method used is normative legal research. The results of the study show that: 1) The effectiveness of PSBB in Ambon city has not been implemented to its full potential. 2) legal protection for the people of Ambon city is more focused on enforcement (repressive) efforts than preventive prevention efforts.